2012
DOI: 10.1177/0022034512438590
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Effect of High-frequency Acceleration on Alveolar Bone

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 29 publications
4
53
1
1
Order By: Relevance
“…Six studies applied in vivo micro-CT, performed in the maxilla [6], [15], [20], [21] and in the condyle [10], [22]. The scanning device which was most often used was the μCT 40 (Scanco Medical, Brüttisellen, Switzerland) [9], [11], [13], [14], [19], [23], [24], [25], [26], [27], [28], [29], [30], [31], followed by the Skyscan apparatus (Skyscan, Aartselaar, Belgium) [3], [4], [8], [20], [21], [32], [33], [34], [35]. The results of the quantitative analysis are presented in Table 2, Table 3, Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies applied in vivo micro-CT, performed in the maxilla [6], [15], [20], [21] and in the condyle [10], [22]. The scanning device which was most often used was the μCT 40 (Scanco Medical, Brüttisellen, Switzerland) [9], [11], [13], [14], [19], [23], [24], [25], [26], [27], [28], [29], [30], [31], followed by the Skyscan apparatus (Skyscan, Aartselaar, Belgium) [3], [4], [8], [20], [21], [32], [33], [34], [35]. The results of the quantitative analysis are presented in Table 2, Table 3, Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the maxillofacial bone and teeth, micro-CT analysis has been mainly used to evaluate alveolar bone remodelling [3], [4], [5], the dynamic changes in periodontal ligament thickness [6] as well as specific osseous sites in the cortical and trabecular bone compartment [7], [8], [9], [10], [11], [12], [13]. However, many of such studies have used micro-CT imaging analyses without detailed description of the applied methodological parameters such as region of interest, the histograms of grey level, the scripts used in the analysis software and the outcome variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that controlled micro-trauma in the form of micro-osteoperforations (MOPs; which maintain the integrity and architecture of hard and soft tissue) will amplify the expression of inflammatory markers that are normally expressed during orthodontic treatment and that this amplified response will accelerate both bone resorption and tooth movement. To test our hypothesis we used MOPs in an animal model of accelerated tooth movement (7) , followed by human clinical trials of the MOPS protocol (8,9).…”
Section: Accelerating Tooth Movementmentioning
confidence: 99%
“…They have shown that vibratory signals promote bone formation, enhance bone density and attenuate the negative effects associated with catabolic stimuli 711 . An anabolic response has also been observed in craniofacial structures 12,13 including the alveolar bone 14 .…”
Section: Introductionmentioning
confidence: 95%